1988
DOI: 10.1002/j.1460-2075.1988.tb02873.x
|View full text |Cite
|
Sign up to set email alerts
|

The S.pombe mei2 gene encoding a crucial molecule for commitment to meiosis is under the regulation of cAMP.

Abstract: The complete nucleotide sequence of the mei2 gene of Schizosaccharomyces pombe, which is essential for initiation of meiosis, is presented and four transcriptional start sites assigned. Transcription of mei2 and other genes involved in life cycle control of S. pombe, which is inducible by nitrogen starvation, is inhibited by addition of cAMP, suggesting that cAMP can mediate the signal of nitrogen supply in S.pombe. mei2 is the furthest downstream among target genes regulated by cAMP and genetic or physiologic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
131
0
1

Year Published

1989
1989
2006
2006

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 176 publications
(139 citation statements)
references
References 31 publications
7
131
0
1
Order By: Relevance
“…Cell numbers were monitored at regular intervals to yield the growth curve illustrated. At the indicated time points (a to e), 50to 200-ml culture samples were withdrawn and used to prepare total RNA. (B) Two separate Northern blots of these five RNA preparations were hybridized with the rasi and byri probes.…”
Section: Resultsmentioning
confidence: 99%
“…Cell numbers were monitored at regular intervals to yield the growth curve illustrated. At the indicated time points (a to e), 50to 200-ml culture samples were withdrawn and used to prepare total RNA. (B) Two separate Northern blots of these five RNA preparations were hybridized with the rasi and byri probes.…”
Section: Resultsmentioning
confidence: 99%
“…Nutritional starvation in combination with the heterozygosity results in the inactivation of a protein kinase encoded by the pat1 gene, which triggers a transition from the mitotic cell cycle to meiosis (Beach et al 1985;Iino & Yamamoto 1985a,b;Nurse 1985;McLeod & Beach 1988;Nielsen & Egel 1990). The mei2 gene product is essential for the initiation of meiosis (Beach et al 1985;Shimoda et al 1985Shimoda et al ,1987Watanabe et al 1988), and is a critical target of Pat1 protein kinase (Watanabe et al 1997). During the mitotic cell cycle, the mei2 gene is expressed only poorly and its gene product undergoes inactivation by Pat1.…”
Section: Introductionmentioning
confidence: 99%
“…Molecular analysis revealed that LHD2 is homologous to maize TE1 that regulates the rate of leaf initiation in corn plants [20]. TE1 displays a significant similarity to Mei2, an RNA-binding protein from Schizosaccharomyces pombe that is required for both premeiotic DNA synthesis and the first reductional division of meiosis [29]. The similarity is highest in the three regions in both protein sequences that encode RNA-recognition motifs (RRMs).…”
Section: Discussionmentioning
confidence: 99%